2016
DOI: 10.1016/j.apsusc.2016.02.106
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of silica colloidal crystal thin films with tuneable structural colours over a wide visible spectrum

Abstract: Colloidal crystal (CC) thin films that produce structural colours over a wide visible spectrum have been self-assembled from silica nanoparticles (SNPs) using a natural sedimentation method. A series of colloidal suspensions containing uniform SNPs (207-350 nm) were prepared using the Stöber method. The prepared silica suspensions were directly subjected to natural sedimentation at an elevated temperature. The SNPs were deposited under the force of gravity and selfassembled into an ordered array. The solid CC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 31 publications
1
58
0
Order By: Relevance
“…The SEM images and tuneable structural colours of such film samples have been reported elsewhere (Gao et al 2016), as seen in Fig. 7.…”
Section: Resultsmentioning
confidence: 66%
“…The SEM images and tuneable structural colours of such film samples have been reported elsewhere (Gao et al 2016), as seen in Fig. 7.…”
Section: Resultsmentioning
confidence: 66%
“…Unsurprising, the opal film self-assembled on glass substrates from populations of uniform SNPs in a particular size range shows vivid structural colours due to the Bragg diffraction of white light caused by the ordered FCC structure of the PC. In our previous work (Gao et al 2016b ), structurally coloured silica opal colloidal crystal films have been fabricated, and it was found that the structural colour effect was tuned by the average diameter of SNPs and viewing angle. However, little has been reported about the structural colour properties of the silica PC on textile fabrics.…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to clarify that the suspensions adopted for colouring these samples were prepared using the SV method; the volumes of the solvent ethanol were 47, 53, 60, 67 and 73 ml. Based on our previous work (Gao et al 2016b ), structurally coloured silica opal films, Fig. 7 a–e, were successfully fabricated in petri dishes using the same silica suspensions prepared from the same recipes for producing the coloured fabrics in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the silica PCs at submicron level contain specific microstructures, and their mechanical properties are affected by both microsphere size and microstructures. Furthermore, the synthesis of these silica PCs has the same porosities intended to be kept as constant (0.26) because of the FCC structure [41], which indicates that the mechanical properties of silica PCs are mainly affected by the variations of particle size and the intrinsic mechanical parameters of microspheres. However, the deformation under the tip is a complex nonlinear process, including elastic and multiple plastic deformations.…”
Section: Deformation Mechanismsmentioning
confidence: 99%